Epidemiologic lessons: Chickenpox outbreak investigation in a rural community around Chandigarh, North India - Mini Pritam Singh; Gagandeep Singh; Amit Kumar; Amarjeet Singh; Radha Kanta Ratho (Wolters Kluwer Medknow Publications, 2011)
Purpose: Primary infection with Varicella Zoster virus (VZV) leads to Varicella or chickenpox. The epidemiology of Varicella has changed dramatically since the introduction of the Varicella vaccine in 1995. The routine childhood immunization in a few countries in the western world like Germany and the United States has reduced the incidence of the disease, associated complications, hospital admissions and deaths related to its complications. However, chickenpox outbreaks are common in naive unvaccinated communities in India. Materials and Methods: We report an outbreak of chickenpox that occurred in a village situated on the outskirts of Chandigarh city in North India in the winter of 2007. The outbreak was confirmed by the detection of VZV IgM by enzyme-linked immunosorbent assay (ELISA) on serum samples from the patients. In patients showing active lesions, Giemsa and indirect immunofluorescence was carried out on scrapings from vesicular lesions. Results: A total of 162 cases occurred in the present outbreak. The serum samples were collected from 20 patients, and all of them showed positive serology for VZV IgM antibodies while 19 showed a positive VZV IgG result by ELISA. The scrapings were collected from two patients showing active lesions, and both were positive by the Tzanck smear examination, and VZV antigen could be demonstrated by immunofluorescence. Conclusions: There is an urgent need to identify naive communities and unvaccinated individuals at risk. Also, there is a need for regular training programmes of health workers posted in peripheral centers so that highly contagious communicable diseases can be picked up in time and such outbreaks can be prevented.